The History and Possibilities of Distributing Music in the 21st Century - Mański, Szymon (Interdisciplinary Studies in Musicology, 2023)
The goal of the present article is to observe the evolution of streaming services, this being one of many prospects for the distribution of alternative music. It would be unrealistic to compare the first of them, which arose at the end of the 1990s, to today’s methods, which provide multiple ways and techniques to support the artists and simultaneously satisfy the hunger for new sounds in audiences. Discussing it from the scientific perspective of studies regarding the legality of musical distribution, in conjunction with the development of the underground music scene, the author – as a musician himself – attempts to introduce the functionality of sound-streaming media as an area for shaping the musical taste of individual listeners, an artistic activity firmly reliant on the cooperation of the artists and their audiences. The article is based on studies conducted by the author in 2021–2023.